2010
DOI: 10.1007/s13197-010-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and pasting properties of starch from stored potato tubers

Abstract: Starch was separated from tubers of four potato (Solanum tuberosum L.) cultivars, viz. 'Kufri Jyoti', 'Kufri Sindhuri', 'Kufri Chipsona-1' and 'Kufri Chipsona-2' before and after 90 days of storage at 4, 8, 12 and 16°C and, morphological, physico-chemical and pasting properties were studied. Scanning electron microscopy showed oval and irregular shaped starch granules with average diameter of 15 μm, and the granule diameter increased after storage. Peak viscosity was lower after storage at 8°C and higher at 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…To alleviate the problem, research has been focused on decreasing the content of total reducing sugars in potato tubers as the most effective method to decrease acrylamide content in fried potatoes (Muttucumaru et al 2008). CIS has been widely studied in potato tubers (Foukaraki et al 2016;Mehdi et al 2013;Wiberley-Bradford et al 2016), and it has been reported that CIS occurs due to an imbalance between the metabolism of starch and sugar (Ezekiel et al 2010). The degradation pathway from starch to hexoses is complex, and several enzymes are involved in this progress, including sucrose synthase (SuSy), sucrose phosphate synthase (SPS), ADP-glucose pyrophosphorylase small subunit (AGPase), granulebound starch synthase (GBSS) (Wiberley-Bradford et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate the problem, research has been focused on decreasing the content of total reducing sugars in potato tubers as the most effective method to decrease acrylamide content in fried potatoes (Muttucumaru et al 2008). CIS has been widely studied in potato tubers (Foukaraki et al 2016;Mehdi et al 2013;Wiberley-Bradford et al 2016), and it has been reported that CIS occurs due to an imbalance between the metabolism of starch and sugar (Ezekiel et al 2010). The degradation pathway from starch to hexoses is complex, and several enzymes are involved in this progress, including sucrose synthase (SuSy), sucrose phosphate synthase (SPS), ADP-glucose pyrophosphorylase small subunit (AGPase), granulebound starch synthase (GBSS) (Wiberley-Bradford et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2018) found that the amylose content varied widely from 6.5 to 32.2% among diverse Indian potato cultivars. Other researchers revealed the amylose content was changeable to some extent due to the difference in potato cultivars (Ezekiel et al 2010;Kim et al 1995;Šimková et al 2013;Wiesenborn et al 1994). As all the potato starches used in this study were manufactured mostly from ''Konafubuki'', we attempted to compare the present data to the previous ones for ''Konafubuki''.…”
Section: Discussionmentioning
confidence: 81%
“…It is generally recognized that the phosphorus content in potato starch is the principal factor contributing to pasting properties. For example, previous reports indicated that the phosphorus content was positively correlated with PV and BD (Ezekiel et al 2010;Karim et al 2007;Noda et al 2004a, b). Our previous report indicated that the phosphorus content was significantly and negatively correlated The data are mean ± standard deviation of three determinations, and the same letter does not show significant difference among samples at p \ 0.05 with PVT (Noda et al 2004a), whereas another study revealed no significant correlation between the phosphorus content and PVT (Karim et al 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since there are few studies with different Peruvian carrot genotypes and limited information about its starch, it is necessary to elucidate this component behavior in new genotypes because several studies indicate significant differences between the genotypes of other species such as potato and cassava (Ezekiel et al, 2010;Charoenkul et al, 2011). So, the aim of this study was to evaluate new Peruvian carrot clones regarding production and starch properties as strategy to increase this species use.…”
Section: Introductionmentioning
confidence: 99%